Advancing understanding on industrial relations in multinational companies: Key research challenges and the INTREPID contribution. (April 2015) - Gunnigle, Patrick; Pulignano, Valeria; Edwards, Tony; Belizón, María J; Navrbjerg, Steen; Olsen, Karen M; Susaeta, Lourdes
This paper has three principal aims. It firstly provides some theoretical background on the key current research issues and challenges in regard to industrial relations in multinational companies. It then presents a concise review of scholarship to date on industrial relations in multinational companies using INTREPID ( Investigation of Transnationals' Employment Practices: an International Database ) data. Finally, the paper identifies some of the main industrial relations issues that remain to be addressed, in effect charting a form of research agenda for future work using the INTREPID data, with particular focus on the potential contribution from 'late joiners' to the INTREPID project.